Systemic prime exacerbates the ocular immune response to heat-killed Mycobacterium tuberculosis. (October 2022) - Pepple, Kathryn L.; John, Sarah; Wilson, Leslie; Wang, Victoria; Van Gelder, Russell N.
Abstract: Post-infectious uveitis describes the condition of chronic immune mediated ocular inflammation associated with pathogens such as Mycobacterium tuberculosis (Mtb). Mtb associated post-infectious uveitis can be modeled in mice by intravitreal injection of heat-killed Mtb (HKMtb). To better understand how prior systemic exposure to the pathogen alters the local immune response to Mtb, we used flow cytometry and multiplex ELISAs to compare ocular responses to intravitreal HKMtb in the presence or absence of a systemic "prime" of HKMtb. Priming resulted in exacerbation of local inflammation with significantly increased clinical and histologic inflammation scores and increased vitreous cytokines concentrations one day after intravitreal injection of HKMtb. Seven days after injection, uveitis in unprimed animals had largely resolved. In contrast in primed animals, clinical signs of chronic inflammation were associated with a significant increase in the number of ocular T cells, NK cells, and Ly6C hi macrophages and increasing vitreous concentrations of IL-17, VEGF, MIG(CXCL9), IP-10(CXCL10), IL-12p40 and MIP-1α(CCL3). In mice lacking mature T and B cells (RAG2 deficient), the impact of priming on the ocular immune response was ameliorated with significantly lower vitreous cytokine concentrations and spontaneous resolution of uveitis. Altogether these results suggest that the ocular response to Mtb is exacerbated by prior systemic Mtb infection and chronic post-infectious uveitis is mediated by local production of cytokines and chemokines that amplify Th17 and Th1 responses. This mouse model of chronic Mtb associated uveitis will help elucidate mechanisms of disease in patients with post-infectious uveitis. Highlights: Priming generates an adaptive immune response that prevents spontaneous resolution of acute pathogen associated molecular pattern (PAMP) induced uveitis. T cells, NK cell, and Ly6C hi macrophages are significantly increased in eyes that develop chronic Mycobacterium tuberculosis PAMP associated uveitis in mice. Vitreous concentrations of IL-17, VEGF, MIG(CXCL9), IP-10(CXCL10), IL-12p40 and MIP-1α(CCL3) increase significantly in eyes that developed chronic uveitis. Priming generates an adaptive immune response that prevents resolution of an acute PAMP induced uveitis. T cells, NK cells, and Ly6C hi macrophages are increased in eyes that develop chronic HKMtb PAMP associated uveitis in mice. Vitreous IL-17, VEGF, MIG(CXCL9), IP-10(CXCL10), IL-12p40 and MIP-1α(CCL3) increase in eyes with chronic uveitis.